(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The homeland of the cabbage crop is considered to be the coast of the Mediterranean Sea and belongs to the category of very ancient crops. Although the composition of cabbage is not rich in nutrients, but is a source of minerals, vitamins and especially vitamin C. But the cabbage crop is also greatly harmed by the disease. These diseases cause not only a decrease in the yield of cabbage, but also a decrease in its quality. That is why it is important to develop effective measures against diseases caused by harmful organisms, while increasing the yield and improving the quality of these crops.